2009
DOI: 10.1007/s11433-009-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Advances in high-resolution nuclear magnetic resonance methods in inhomogeneous magnetic fields using intermolecular multiple quantum coherences

Abstract: Strong and extremely homogeneous static magnetic field is usually required for high-resolution nuclear magnetic resonance (NMR).However, in the cases of in vivo and so on, the magnetic field inhomogeneity owing to magnetic susceptibility variation in samples is unavoidable and hard to eliminate by conventional methods such as shimming. Recently, intermolecular multiple quantum coherences (iMQCs) have been employed to eliminate inhomogeneous broadening and obtain high-resolution NMR spectra, especially for in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Among various candidates for implementing the large-scale quantum computer in the future and demonstrating quantum algorithms to corroborate existing theories, nuclear magnetic resonance (NMR) has been proven to be a convenient and practical method to learn lessons for the other physical systems [5][6][7][8][9][10][11][12][13][14][15][16] , though it has been a powerful tool in biology and chemistry research as well [17,18] . NMR quantum computer is an Ising-type computer [19] where two-body interactions take the form of π 2 i j ij z z J   , known as J-couplings in NMR, where i z  denotes the Pauli matrix of the i-th spin, and J ij denotes the strength of coupling between the two spins.…”
mentioning
confidence: 99%
“…Among various candidates for implementing the large-scale quantum computer in the future and demonstrating quantum algorithms to corroborate existing theories, nuclear magnetic resonance (NMR) has been proven to be a convenient and practical method to learn lessons for the other physical systems [5][6][7][8][9][10][11][12][13][14][15][16] , though it has been a powerful tool in biology and chemistry research as well [17,18] . NMR quantum computer is an Ising-type computer [19] where two-body interactions take the form of π 2 i j ij z z J   , known as J-couplings in NMR, where i z  denotes the Pauli matrix of the i-th spin, and J ij denotes the strength of coupling between the two spins.…”
mentioning
confidence: 99%
“…However, in the presence of field distortions caused by susceptibility gradients, line broadenings occur in these 2D spectra, for the routine 2D MRS such as COSY and J-RES, both t 1 and t 2 periods are conventional SQC evolution. We have demonstrated that in above two kinds of spectra the tilt angles of the inhomogeneous broadenings and the chemical shift alignment (of diagonal peaks for the COSY case) orient at the same direction in the 2D spectra [28], resulting in the overlapping of adjacent resonances. Thus the metabolite quantification is seriously influenced.…”
Section: Introductionmentioning
confidence: 86%
“…In a very recent work, 19 Pelupessy and co-workers used coherence transfers between spins such as the SECSY sequence instead of spatially-dependent z-rotations 15,16 to compensate inhomogeneities with a modified single-shot 2D spectroscopy using the adiabatic sweep for encoding. 20,21 Theoretically, coherence/polarization transfers between spins can compensate arbitrary field inhomogeneities with larger spatial scales than the distance between coupled spins, 22 so that the new method is also promising in in vivo applications with randomly distributed magnetic field gradients.…”
Section: Introductionmentioning
confidence: 99%